Innovative Marketing Strategies and Entrepreneurial Approaches in Promoting Halal Tourism Destinations: A Systematic Literature Review - Setiawan, Harry (International Journal of Economic, Finance and Business Statistics, 2024)
This study aims to conduct a systematic literature review on the role of innovative marketing strategies and entrepreneurial approaches in promoting halal tourism destinations, and their influence on the perceptions, behaviors, and intentions of Muslim and non-Muslim tourists. By reviewing 65 publications obtained from the Scopus database, this study identifies research trends, key focus areas, and gaps in the existing literature. The findings highlight the increasing trend of research on this topic, the most influential journals and researchers, and the geographical distribution of studies. The review also reveals the importance of innovative marketing and entrepreneurial strategies in attracting diverse tourist segments and enhancing the competitiveness of halal tourism destinations. Based on the identified gaps, future research directions are proposed to further advance the understanding of this field.